The class II HD-ZIP JAIBA gene is involved in meristematic activity and important for gynoecium and fruit development in Arabidopsis - Zúñiga-Mayo, Victor M. (Landes Bioscience, 2012)
Development and patterning of the gynoecium – and later the fruit – must be finely regulated to ensure the survival of the species that produces them. The process that leads to successful fruit formation starts at early stages of floral meristem development and follows a series of chronologically successive events. In a recent work we reported the functional characterization of the class II HD-ZIP JAIBA (JAB) gene. Mutant jab plants showed sporophytic defects in male and female reproductive development, and combined with the mutant crabs claw (crc) caused defects in the floral meristem (FM) determination process and gynoecium medial tissue development. Furthermore, the JAB protein interacted with transcription factors known to regulate meristematic activity, fruit development and FM determinacy. Preliminary results presented here suggest a genetic interaction between JAB and the gene SHOOT MERISTEMLESS (STM).